Categories and orthodoxies in studies on culture and femicide: An ethno-informed route to knowledge - Ryen, Anne (Journal of Comparative Social Work, 2018)
This article is a methodological discussion, in which I argue that to study complex phenomena such as culture and femicide calls for other approaches other than the dominant interview and survey studies. By their focus on the contextual, the interactional and the process itself, and by rejecting language as referential and transparent, ethno-informed approaches better recognize and capture this complexity. To see the interview as a social interactional event grounded in a world of common-sense thinking makes members of a society share a common stock of knowledge, or a social world and communicative understanding. This is particularly relevant in cross-cultural studies, in which we can no longer assume that members share such common-sense thinking. This makes activities such as asking questions and filling answers into categories problematic. We need to see how a phenomenon such as femicide, telling stories about it and our representations reflect the diversity of cultural forms. I will draw on secondary data to illustrate my arguments and their relevance.